Impact of Pre-Anthesis Drought Stress on Physiology, Yield-Related Traits, and Drought-Responsive Genes in Green Super Rice - Ahmad, Hassaan; Zafar, Syed Adeel; Naeem, Muhammad Kashif; Shokat, Sajid; Inam, Safeena; Rehman, Malik Attique ur; Naveed, Shahzad Amir; Xu, Jianlong; Li, Zhikang; Ali, Ghulam Muhammad; Khan, Muhammad Ramzan (Frontiers in Genetics, 2022)
Optimum soil water availability is vital for maximum yield production in rice which is challenged by increasing spells of drought. The reproductive stage drought is among the main limiting factors leading to the drastic reduction in grain yield. Objective of this study was to investigate the molecular and morpho-physiological responses of pre-anthesis stage drought stress in green super rice. The study assessed the performance of 26 rice lines under irrigated and drought conditions. Irrigated treatment was allowed to grow normally while drought stress was imposed for 30 days at pre-anthesis stage. Three important physiological traits including pollen fertility percentage (PFP), cell membrane stability (CMS) and normalized difference vegetative index (NDVI) were recorded at anthesis stage during the last week of drought stress. Agronomic traits of economic importance including grain yield were recorded at maturity stage. The analysis of variance demonstrated significant variation among the genotypes for most of the studied traits. Correlation and principal component analyses demonstrated highly significant associations of particular agronomic traits with grain yield, and genetic diversity among genotypes, respectively. Our study demonstrated a higher drought tolerance potential of GSR lines compared to local cultivars, mainly by higher pollen viability, plant biomass, CMS, and harvest index under drought. In addition, the molecular basis of drought tolerance in GSR lines was related to upregulation of certain drought responsive genes including OsSADRI, OsDSM1, OsDT11 but not the DREB genes. Our study identified novel drought responsive genes (LOC_Os11g36190, LOC_Os12g04500, LOC_Os12g26290 and LOC_Os02g11960) that could be further characterized using reverse genetics to be utilized in molecular breeding for drought tolerance.